Schools ruled by measurement results: School effectiveness and educational policies during the transition to democracy, Chile 1990-2017 - Juan F. Herrera Jeldres; Universidad de Chile; Leonora Reyes-Jedlicki; Universidad de Chile; Carlos M. Ruiz Schneider; Universidad de Chile (Escuela de Psicología, Pontificia Universidad Católica de Valparaíso, 2018)
The governments of the Chilean democratic transition understood the task of re-democratizing the educational system based on the imperative of quality and equity. This study analyzes the grounding concepts of educational policies established in the democratic transition in Chile (1990-2017). It postulates that school effectiveness is the articulating element of these policies, a theoretical and ideological discourse related to a complex discursive plot, coupled with more general transformations of the State, also called second generation reforms. This study uses a qualitative documentary method analysis, and intellectual history and the theory of ideology as data analysis techniques. Among the results emerges the generalization of new public management process, subjecting the institutions to a new form of control and internal competition. It is concluded that school effectiveness is based on a research model that reduces the social complexity of education to the measurement, which is functional to governments that seek consensus and that are not oriented to social change or to the construction of more egalitarian, instituting, in this way, technical answers to political problems.